GAMBARAN UMUM PENANGANAN CEDERA PADA SAAT AKTIVITAS OLAHRAGA (Studi Kasus Pada Atlit Futsal Club The Boom) - Syahadatina Syahadatina (Universitas Syiah Kuala, 2022)
The purpose of the study. The purpose of writing this literature review is: To find out the general description of the handling of injuries during sports activities (case studies on futsal athletes).Materials and methods. This study uses a design that is a literature review with a PICOS approach: (1) P (problem), (2) I (intervention), (3) C (control), (4 ) O (outcome) is a method of seeking clinical information and (4) Study Design.Results. The results of a literature review search through the google scholar and freefullpdf.com databases using the keywords handling sports injuries, in the search the authors found three journals and then these journals will become a literature review. Based on a literature review from three journals, it can be concluded that the general description of handling sports injuries, namely, handling at the time of injury can use the RICE and PRICES methods, but post-injury it is recommended to use warm and cold therapy, as well as therapeutic modalities. To prevent injuries to bones, joints and muscles, players need to take some precautions. These preventive measures can be done by warm up by doing stretching before starting the match. When the match is over, the athlete must cool down.Conclusions. The higher the knowledge about handling injuries that a person has, the more fatal sports injuries will be.